2009
DOI: 10.1111/j.1365-313x.2009.03977.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall glucomannan in Arabidopsis is synthesised by CSLA glycosyltransferases, and influences the progression of embryogenesis

Abstract: SUMMARYMannans are hemicellulosic polysaccharides that have previously been implicated as structural constituents of cell walls and as storage reserves but which may serve other functions during plant growth and development. Several members of the Arabidopsis cellulose synthase-like A (CSLA) family have previously been shown to synthesise mannan polysaccharides in vitro when heterologously expressed. It has also been found that CSLA7 is essential for embryogenesis, suggesting a role for the CSLA7 product in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
210
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 194 publications
(216 citation statements)
references
References 57 publications
(150 reference statements)
4
210
0
2
Order By: Relevance
“…As almost all Man detected in cell wall preparations in Arabidopsis is glucomannan derived (Goubet et al, 2009), this result indicates that these mutants have reduced levels of glucomannan in their cell walls. To confirm the changes in cell wall glucomannan, polysaccharide analysis using carbohydrate gel electrophoresis (PACE) was also performed (Goubet et al, 2002(Goubet et al, , 2009). Here, cell wall (AIR, for alcohol-insoluble residue) was prepared from seedlings and hydrolyzed by a combination of b-1,4-mannanases.…”
Section: Amount and Structure Of Cell Wall Glucomannanmentioning
confidence: 92%
See 1 more Smart Citation
“…As almost all Man detected in cell wall preparations in Arabidopsis is glucomannan derived (Goubet et al, 2009), this result indicates that these mutants have reduced levels of glucomannan in their cell walls. To confirm the changes in cell wall glucomannan, polysaccharide analysis using carbohydrate gel electrophoresis (PACE) was also performed (Goubet et al, 2002(Goubet et al, , 2009). Here, cell wall (AIR, for alcohol-insoluble residue) was prepared from seedlings and hydrolyzed by a combination of b-1,4-mannanases.…”
Section: Amount and Structure Of Cell Wall Glucomannanmentioning
confidence: 92%
“…However, if GDP-glucose (GDP-Glc) is also provided, a glucomannan backbone is produced (a combination of b-1,4-Man and b-1,4-Glc; Liepman et al, 2005). In Arabidopsis, as shown in the csla2 csla3 csla9 triple mutant, loss of glucomannan in inflorescence stems has no apparent effect on growth and development (Goubet et al, 2009). However, glucomannan seems to play a specific role in certain cell types, as plants lacking an active CSLA7 are embryo lethal (Goubet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because glucomannan is a minor hemicellulose of the primary cell wall, it is perhaps surprising that proteins implicated in glucomannan synthesis were quantified by this method. CslA2 (rank 91) is a GT2 member that is required for glucomannan backbone synthesis (Liepman et al, 2005;Goubet et al, 2009). Mannan SynthesisRelated1 (MSR1; rank 58) and MSR2 (rank 19) are putative glycosyltransferases of the GT65R family involved in glucomannan production, but their exact biochemical role is unclear (Wang et al, 2012).…”
Section: Quantities Of the Cell Wall Synthesis Machineries In The Golmentioning
confidence: 99%
“…These enzymes polymerize the b-1,4-linked backbone of mannans or glucomannans, depending on the substrates (GDP-Man and/or GDP-Glc) provided (Richmond and Somerville, 2000;Liepman et al, 2005Liepman et al, , 2007Pauly et al, 2013). In Arabidopsis (Arabidopsis thaliana), nine CSLA genes have been identified; different CSLAs are responsible for the synthesis of different mannan types (Liepman et al, 2005(Liepman et al, , 2007 mannan synthase activity in vitro (Liepman et al, 2005) and has been shown to synthesize stem glucomannan in vivo (Goubet et al, 2009). Disrupting the CSLA7 gene results in defective pollen growth and embryo lethality phenotypes in Arabidopsis, indicating structural or signaling functions of mannan polysaccharides during plant embryo development (Goubet et al, 2003).…”
mentioning
confidence: 99%
“…A mutation in CSLA9 results in the inhibition of Agrobacterium tumefaciens-mediated root transformation in the rat4 mutant (Zhu et al, 2003). CSLA2, CSLA3, and CSLA9 are proposed to play nonredundant roles in the biosynthesis of stem glucomannans, although mutations in CSLA2, CSLA3, or CSLA9 have no effect on stem development or strength (Goubet et al, 2009). All of the Arabidopsis CSLA proteins have been shown to be involved in the biosynthesis of mannan polysaccharides in the plant cell wall (Liepman et al, 2005(Liepman et al, , 2007, although the precise physiological functions of only CSLA7 and CSLA9 have been conclusively demonstrated.…”
mentioning
confidence: 99%